2004
DOI: 10.1071/ea03208
|View full text |Cite
|
Sign up to set email alerts
|

Application of phosphate rock, with or without Aspergillus awamori inoculation, to meet phosphorus demands of rice - wheat systems in the Indo - Gangetic plains of India

Abstract: A 3-year field experiment beginning in 1995–96 was undertaken on a Gangetic alluvial soil (Typic Ustochrept) at Modipuram, India, to examine how phosphorus (P) demands of rice–wheat cropping systems might be met with heavy initial dressings of phosphate rock. Treatments were: (i) 1 rice–wheat cycle where P was applied as phosphate rock to each successive rice crop (54 kg P/ha i.e. 27 kg P/ha to rice and 27 kg P/ha to wheat); (ii) 2 rice–wheat cycles where P was applied as phosphate rock to alternate rice crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
5
13
0
Order By: Relevance
“…The yield observation resembles the findings of Gholami et al [4] that application of PSM Pseudomonas and Azospirillum increases the yield in grains per plant by 44% over control. This was in agreement to Dwivedi et al [5] observation that presowing inoculation of wheat grains with PSM led to increase in yield over non-inoculated treatments. The increase in ear head length, number of spikelets and grains resembles the earlier findings of Algawadi [6] while working with sorghum involving the co-inoculation of Trichoderma harzianum and Pseudomonas striata.…”
Section: Discussionsupporting
confidence: 93%
“…The yield observation resembles the findings of Gholami et al [4] that application of PSM Pseudomonas and Azospirillum increases the yield in grains per plant by 44% over control. This was in agreement to Dwivedi et al [5] observation that presowing inoculation of wheat grains with PSM led to increase in yield over non-inoculated treatments. The increase in ear head length, number of spikelets and grains resembles the earlier findings of Algawadi [6] while working with sorghum involving the co-inoculation of Trichoderma harzianum and Pseudomonas striata.…”
Section: Discussionsupporting
confidence: 93%
“…In the present investigation, the decline in crop productivity under RDF may also explained in terms of greater NO 3 -N leaching beyond the root zone (beyond a soil depth of 45 cm) ( Figure 4), and depletion of soil exchangeable K and available S contents (Tables 7 and 8). These results are corroborated by earlier reports of other long-term experiments wherein the emergence of multi-nutrient deficiencies [11] led to a yield decline over the passage of time, and the supply of different nutrients in adequate amounts helped to attain yield stability [16,47].…”
Section: Rws Productivitysupporting
confidence: 89%
“…In an intensive RWS, nutrient removal often exceeds replenishment through fertilizers [12][13][14][15][16]. LTEs continuing under diverse agro-ecologies in India underlined that neither the fertilizers nor the organic sources in isolation can achieve sustainable production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saad and Hammad (1998) reported that the greatest grain yield of wheat was found with inoculation of bacteria and application of calcium superphosphate. These results were also in conformity with the findings of Dwivedi et al (2004) who reported that pre sowing inoculation of wheat seeds with phosphate solubilizing microorganisms led to a yield increase over noninoculated treatments. Effects on P uptake by wheat Total P uptake by wheat was significantly influenced by the different treatments with three soils (Table 3 and Fig.…”
Section: Resultssupporting
confidence: 81%